2018
DOI: 10.5604/01.3001.0012.6668
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shot peening on microstructure, hardness, and corrosion resistance of AISI 316L

Abstract: Purpose: This research conducted to analyse the effect of shot peening on surface structure, hardness, and resistance to corrosion of AISI 316L. Design/methodology/approach: The shot peening process is carried out on the surface of 316L stainless steel samples with four peening durations, and they are 2, 4, 15, and 30 minutes. Shot ball steel with diameter 0.4 mm for metal shot blasting and model S110 of ISO 11124/3 and SAEJ827, with the chemical composition, are C (0.8-1.2 wt.%), Mn (0.6-1.2 wt.%), Si (min. 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
0
10
0
5
Order By: Relevance
“…Previous studies [ 12 , 13 , 14 ] have also shown that the defect distribution in LPBF parts is mainly focused on the near surface areas. Shot peening (SP) has been successfully utilized for different types of conventional austenitic stainless steels to create heavy surface deformation or even surface grain refinement up to nano-scale grain size for improved mechanical properties [ 15 , 16 , 17 ]. SSP can also induce martensite transformation on the surface [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [ 12 , 13 , 14 ] have also shown that the defect distribution in LPBF parts is mainly focused on the near surface areas. Shot peening (SP) has been successfully utilized for different types of conventional austenitic stainless steels to create heavy surface deformation or even surface grain refinement up to nano-scale grain size for improved mechanical properties [ 15 , 16 , 17 ]. SSP can also induce martensite transformation on the surface [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the main effects of the use of surface plastic deformation methods are provided both by directly increasing the strength of the surface layer [8] and by inducing compressive residual stresses [9]. However, the cited studies do not pay attention to technological stress concentrators, which can have an equally significant effect on the endurance limit.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Belirtilen değişkenler ile yapılan denemeler sonrasında en uygun bilyalama parametreleri 50mm nozül mesafeli, 4 𝑘𝑔/𝑐𝑚 2 basınç değeri, 60° açı ile parça üzerine 130 saniye boyunca gönderilen bilyalar sonucunda elde edilmiştir. Alüminyum implantlarda faklı bilyalama sürelerine göre parçaların korozyon oranlarını incelemişlerdir ve uygun bilyalama süresini 2 dakika olarak saptamışlardır (Iswanto et al 2020). Otomotiv ve havacılık sektöründe kullanılan AA2024 alüminyum malzemenin çinko bilyalar yardımı ile farklı süreler altında sertlik değerlerinin değişimini incelemişlerdir.…”
Section: Afyon Kocatepe üNiversitesi Fen Ve Mühendislik Bilimleri Der...unclassified